h - Qin, Dahe.; Ding, Yongjian; Mu, Mu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
Through numerous color figures and tables, this book presents the most up-to-date knowledge on climate and environmental change in China. It documents the evidence and attribution of climate and environmental changes in the past few decades and discusses the impacts of climate change on environments, economy, and society. The book further provides projections of climate change and its impacts in the future. Finally, it offers the climate change mitigation and adaption technologies with strategic options which will be of interest for policy makers, researchers and the general public as well.
Climate, Environmental, and Socio-economic Characteristics of China -- Climatic and Environmental Changes in China -- The Attribution of Climate Change and its Uncertainty -- Impacts of ClimateChange on the Environment, Economy, and Society of China -- Projections of Climate Change and its Impacts -- Climate Change Mitigation and Adaptation Technology and Policy Options -- Strategic Options to Address Climate Change -- Concluding Remarks.
Keywords: Environment; Climate change; Environment; Climate Change; Climate Change/Climate Change Impacts; Climate Change Management and Policy; Electronic books